ANALISIS KELAYAKAN USAHATANI TUMPANGSARI CABAI-JAGUNG DAN CABAI-TEMBAKAU LAHAN KERING DI DESA KAMPUNGBARU, KECAMATAN JOMBANG, KABUPATEN JOMBANG (Feasibility Analysis of Chili-Corn and Chili-Tobacco Intercropping Farming in Kampungbaru Village, Jombang District, Jombang Regency) - FAUZI, FA'ACHSANI INATSAN; FIRDAUS, MOCHAMAD ILHAM; INDRIATI, EFFY (Universitas Mulawarman (University of Mulawarman), 2026)
This study aims to analyse the most profitable intercropping commodities on dry land in Kampungbaru Village, Plandaan Subdistrict, Jombang Regency. The research was conducted purposively from May to July 2025 on 63 farmers who practised intercropping of chilli and maize and chilli and tobacco. Primary data were collected through observation and interviews, while secondary data were obtained from relevant agencies. The analysis used calculations of production costs, revenue, income, Revenue Cost (R/C) ratio, and Benefit Cost (B/C) ratio. The results showed that chilli–tobacco had higher total costs than chilli–maize, but provided greater revenue and income. The R/C ratio and B/C ratio values for chilli–maize were 3.49 and 2.49, while those for chilli–tobacco were 4.59 and 3.59, indicating that both systems were feasible to implement, with higher values for chilli–tobacco. These findings indicated that pepper–tobacco intercropping was more profitable and had the potential to improve the welfare of dryland farmers.